2013
DOI: 10.3168/jds.2012-5597
|View full text |Cite
|
Sign up to set email alerts
|

Associations between locomotion score and kinematic measures in dairy cows with varying hoof lesion types

Abstract: During this study we explored the gait attributes commonly used in subjective locomotion scoring systems and use new technology to evaluate these gait attributes objectively on 60 Holstein lactating dairy cattle. Kinematic gait analysis more commonly used in sports and equine science was adapted for use on dairy cattle to assess stride characteristics, joint flexion, and spine posture in dairy cows with different lameness status. Cows that were lame had shorter stride length and had negative tracking distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 20 publications
(29 reference statements)
5
29
1
1
Order By: Relevance
“…yellow circles) attached to hooves, limb joints, withers, or back-line contour. Video recordings of cows walking with markers are later analysed with software for kinematic variables (Flower et al, 2005;Aoki et al, 2006;Blackie et al, 2013). Another technique uses image preprocessing, in which video recordings are transformed into sequences of binary images to facilitate the detection of anatomical parts of cows (Song et al, 2008;Van Hertem et al, A c c e p t e d M a n u s c r i p t 2013; Viazzi et al, 2013).…”
Section: Automatic Locomotion Scoring Systemsmentioning
confidence: 99%
“…yellow circles) attached to hooves, limb joints, withers, or back-line contour. Video recordings of cows walking with markers are later analysed with software for kinematic variables (Flower et al, 2005;Aoki et al, 2006;Blackie et al, 2013). Another technique uses image preprocessing, in which video recordings are transformed into sequences of binary images to facilitate the detection of anatomical parts of cows (Song et al, 2008;Van Hertem et al, A c c e p t e d M a n u s c r i p t 2013; Viazzi et al, 2013).…”
Section: Automatic Locomotion Scoring Systemsmentioning
confidence: 99%
“…This suggestion is in line with earlier studies, which showed that back curvature was one of the main indicators for locomotion scoring (Sprecher et al, 1997;Van Nuffel et al, 2009). Back curvature is also considered to be a reliable measure for lameness classification (Blackie et al, 2013;Hoffman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Back curvature can be extracted from images by different feature variables, such as an inverse radius Viazzi et al, 2014), different curvature angles ) and a back posture measurement (BPM) . The strong relation between back arch and gait abnormality is proven (Sprecher et al, 1997;Blackie et al, 2013;Hoffman et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Another group researcher reported that fully automated lameness detection system using load cells (Rajkondawar, U., et al [35], Pastell, M., et al [36], Liu, J., et al [37]). Another group researcher is also study about cattle lameness detection system using computer vision [38][39][40][41][42]. The system report lame cattle in need of treatment must be separated from the herd automatically.…”
Section: Health Observationmentioning
confidence: 99%
“…Sato, S., et al [49], developed bolus-type wireless sensor nodes which were inserted into the rumen using a special instrument via the cow's oral cavity. The ruminal pH was measured and stored every 15 minutes and this information was then transmitted wirelessly [40]. The sensor can be used continuously for a period of two to three months without replacing the battery, and can be recovered orally with special instruments.…”
Section: Health Observationmentioning
confidence: 99%